EPEN-46. DNA METHYLATION LANDSCAPE OF RECURRENT PEDIATRIC EPENDYMOMA IDENTIFIES KEY DRIVER EVENTS. (4th December 2020) - Zhao, Sibo; Li, Jia; Zhang, Huiyuan; Qi, Lin; Du, Yuchen; Kogiso, Mari; Braun, Frank; Lindsay, Holly; Genevini, Paola; Veillard, Anne-Clemence; Schvartzman, Sol; Laczik, Miklos; et al.
Abstract: Pediatric ependymoma has a propensity of developing late and multiple relapses over many years. About 50% of patients will experience relapses and eventually succumb to their disease. Our study is aimed to understand the mechanism of resistance and drivers associated with pediatric ependymoma relapse. We developed 10 sets of patient-derived orthotopic xenograft (PDOX) models of recurrent pediatric ependymoma from both RELA and PFA tumors. Time from primary tumor to last recurrence ranges from 2.75 – 13 years. Number of recurrences per patient ranges from 1 – 7 times. We performed Reduced Representation Bisulfite Sequencing (RRBS) and Whole Genome Bisulfite Sequencing (WGBS) to map the DNA methylation landscape of total of 30 samples of matched primary and recurrent tumors. Molecular subtypes and DNA methylation profiles were maintained, and RELA/PFA signature genes showed similar expression pattern during serial relapses. RELA- and PFA-specific Differentially Methylated CpGs (DMCs) are identified from primary tumors. During the recurrent process, individual patients displayed consistent changes of DMCs and shared DMCs among patients became convergent. We then identified shared common specific DMCs in recurrent RELA and PFA tumors that emerged as the driver signatures. We found that these recurrent DNA methylation signatures could be identified from primary tumors. Our analysis of the PDOX models showed that they can mostly recapitulate humor tumors' DNA methylation and we were able to identify shared recurrent specific DMCs associated genes in PDOX models. Our comprehensive data is the first of its kind aimed to investigate the epigenetic mechanisms during pediatric ependymoma recurrence.